THE EXTENT OF THE EFFECTIVENESS OF APPLYING BANKING GOVERNANCE PRINCIPLES IN DEVELOPING INTERNAL AUDITING IN PRIVATE IRAQI BANKS - Dr. Mohammad Abdulwahid Jayyas (Scholar Express Journals, 2025)
This study investigates the effect of banking governance principles such as transparency, accountability, independence, adherence to international auditing standards and oversight on the effectiveness of internal auditing in private banks in Iraq
Keywords: Banking Governance; Internal Auditing